2019
DOI: 10.3389/fmicb.2019.00319
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Approach to Characterizing Disease Epidemiology in a Disease-Endemic Environment in Northern Thailand

Abstract: In this study, we used a metagenomic approach to analyze bacterial communities from diverse populations (humans, animals, and vectors) to investigate the role of these microorganisms as causative agents of disease in human and animal populations. Wild rodents and ectoparasites were collected from 2014 to 2018 in Nan province, Thailand where scrub typhus is highly endemic. Samples from undifferentiated febrile illness (UFI) patients were obtained from a local hospital. A total of 200 UFI patient samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…Subsequently the BAPGM platform has been used diagnostically to assess bloodstream infection in dogs, other animal species, [37,38] and in humans [19,20,[39][40][41]. It is clear that the developmental and microbiological utilization of more sensitive or robust microbiological techniques such as MALDI TOF, Next Generation Sequencing and specialized enrichment/PCR techniques enhance the detection of microorganisms in various patient samples [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently the BAPGM platform has been used diagnostically to assess bloodstream infection in dogs, other animal species, [37,38] and in humans [19,20,[39][40][41]. It is clear that the developmental and microbiological utilization of more sensitive or robust microbiological techniques such as MALDI TOF, Next Generation Sequencing and specialized enrichment/PCR techniques enhance the detection of microorganisms in various patient samples [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Since Haemaphysalis ticks are three-host ticks, there is a possibility that our fed tick specimens may have fed on a non-infected rodent before contacting an infected rodent. A recent report by Takhampunya et al (2019) found that the A. bovis pathogen was detected in H. bandicota ticks that were removed from B. indica and Rattus spp. rodents collected in northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough characterisation and monitoring of CVBD is crucial to protect the health of dogs and humans, especially in regions of Asia where there has been little explorative research done into established, emerging and novel CVBDs [2,5]. To address these knowledge gaps, state-of-the-art methodologies could be employed such as next-generation sequencing (NGS) based 16S ribosomal RNA (16S rRNA) metabarcoding that can supersede conventional PCR (cPCR) techniques with regard to their ability to detect and discover rare and/or novel organisms [18,19]. 16S rRNA metabarcoding is better able to elucidate diversity in explorative research by not relying on likely pathogen prevalence in a region nor on a priori knowledge of a pathogen's target genetic sequences, whilst also being better able to characterise coinfection [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…To address these knowledge gaps, state-of-the-art methodologies could be employed such as next-generation sequencing (NGS) based 16S ribosomal RNA (16S rRNA) metabarcoding that can supersede conventional PCR (cPCR) techniques with regard to their ability to detect and discover rare and/or novel organisms [18,19]. 16S rRNA metabarcoding is better able to elucidate diversity in explorative research by not relying on likely pathogen prevalence in a region nor on a priori knowledge of a pathogen's target genetic sequences, whilst also being better able to characterise coinfection [18,20]. Previous work has already developed a novel 16S and 18S rRNA metabarcoding methodology to characterise the range of blood-borne bacterial, apicomplexan and kinetoplastid organisms infecting canine hosts in Thailand, a country of substantial CVBD diversity [4,8,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%